Bridging the Gap: Exploring Practices and Challenges for Including Children with Disabilities in Mainstream Classroom - Baraily, Khagendra; Chalaune, Bhawan Singh; Sherpa, Dawa (KMC Journal, 2025)
This study aimed to explore the perception of students with disability towards the existing practice of inclusive education in mainstream schools. The qualitative research design along with interpretative phenomenological approach was employed in this study. Four students with disabilities including physical, deaf and children with visual impairment were purposively selected from integrated school located in Kathmandu Valley. In-depth interview was taken through semi-structured interview guidelines. The thematic analysis technique was applied to generate findings. The themes were discussed by linking with prospective and literature. The findings reported as setting disable friendly infrastructure, professional development opportunity for teachers, technology-based instruction and teacher’s collaboration are essential strategies for inclusion. Meaningful inclusive education practices maintain a supportive and equitable learning environment for all types of children including those with disabilities. To implement inclusive practices in the classroom, administrative hurdles, infrastructure barriers, technological barriers, environmental barriers and legislative barriers are the major challenges in practising equity strategies in the classroom. The findings can contribute to set up effective practices for combating such challenges. By using the scope of the study, the policy maker, education planners and teachers can level up appropriate strategies for increasing the access of children with disability in education.